The positive impact on translational research of Fondazione italiana di ricerca per la Sclerosi Laterale Amiotrofica (AriSLA), a non-profit foundation focused on amyotrophic lateral sclerosis. Convergence of ex-ante evaluation and ex-post outcomes when goals are set upfront - Guareschi, Stefania; Ravasi, Maddalena; Baldessari, Danila; Pozzi, Silvia; Zaffino, Tiziana; Melazzini, Mario; Ambrosini, Anna (Frontiers in Research Metrics and Analytics, 2023)
Charities investing on rare disease research greatly contribute to generate ground-breaking knowledge with the clear goal of finding a cure for their condition of interest. Although the amount of their investments may be relatively small compared to major funders, the advocacy groups' clear mission promotes innovative research and aggregates highly motivated and mission-oriented scientists.Here, we illustrate the case of Fondazione italiana di ricerca per la Sclerosi Laterale Amiotrofica (AriSLA), the main Italian funding agency entirely dedicated to amyotrophic lateral sclerosis research. An international benchmark analysis of publications derived from AriSLA-funded projects indicated that their mean relative citation ratio values (iCite dashboard, National Institutes of Health, U.S.) were very high, suggesting a strong influence on the referring international scientific community. An interesting trend of research towards translation based on the 'triangle of biomedicine' and paper citations (iCite) was also observed. Qualitative analysis on researchers' accomplishments was convergent with the bibliometric data, indicating a high level of performance of several working groups, lines of research that speak of progression towards clinical translation, and one study that has progressed from the investigation of cellular mechanisms to a Phase 2 international clinical trial.The key elements of the success of the AriSLA investment lie in: i) the clear definition of the objectives (research with potential impact on patients, no matter how far), ii) a rigorous peer-review process entrusted to an international panel of experts, iii) diversification of the portfolio with ad hoc selection criteria, which also contributed to bringing new experts and younger scientists to the field, and iv) a close interaction of AriSLA stakeholders with scientists, who developed a strong sense of belonging.Periodic review of the portfolio of investments is a vital practice for funding agencies. Sharing information between funding agencies about their own policies and research assessment methods and outcomes help guide the international debate on funding strategies and research directions to be undertaken, particularly in the field of rare diseases, where synergy is a relevant enabling factor.